(untitled) (Discourse of Law and Administration, 2025)
The increasing urban population, financial crises and climate change are just a few of the challenges impacting planning processes in the cities. A response to those challenges is the concept of the smart city, which leverages modern technologies to improve urban functioning across various domains. This article discusses one such technology – digital twins – which can enhance spatial planning processes by allowing for the verification of assumptions based on the real and projected data. The article explores how digital twin technology can impact the level of public participation in the adoption of local spatial development plans and analyzes the current legal framework regarding the use of digital twins, particularly in public consultation processes. It presents a method of integrating the digital twin model into the Polish legal system, emphasizing the potential benefits for community engagement in urban planning.